Center for Athletic Rehabilitation (CARe) a Philippine therapeutic landscape development for injured athletes - Tui, Liezchel G.; Nadal, Cathe Desiree S. (Quezon City College of Architecture, University of the Philippines Diliman, 2014)
The Philippines is a country that lives the idea of its athletes as winners and champions in any sports event. For any sportsman, the real deal breaker in playing their sport is the real risk of injury. Getting injured at play is painful and frustrating time; and the arduous task of recovery may seem like a burden in a stern-feeling rehabilitation facility that addresses only the physical side of an athlete’s recovery. The stress and pressure that push athletes to their very core must be minimized while their body is recovering. Being removed from the sport that they love being a real cause for anxiety among injured athletes, helping the athlete return to compete with confidence after an injury is a true and legitimate concern.
Developing a therapeutic rehabilitation facility that can help treat, encourage, and improve the psychological and physical wellness of injured athletes in the Philippines is the foremost concern that this research aims to address.
Athletes in the Philippines may need a rehabilitation center for a number of myriad reasons that are legitimate; however, there are lot of factors to be considered before they ultimately decide to do so. And so this research may help in ensuring that there is also a psychological incentive apart from the physical one that may encourage them to opt in staying in a landscaped rehabilitation center.
Recovery is the most foremost concern. Being able to access the said site is a factor and so is the kind of environment that the facility can offer. Encouragement from family and friends is a deciding statistic as well that can make or break their decision to go to a rehabilitation center.
The study conducted showed that many athletes are open and interested in the idea of a landscaped athletic rehabilitation center in the Philippines.

Keywords:
Healing, Therapeutic Landscape, Athletic Rehabilitation
Thesis (Bachelor of Landscape Architecture)--University of the Philippines Diliman
Keywords: Athletic Injuries -- rehabilitation; sports rehabilitation